Mixed Small Cell Carcinoma and Adenocarcinoma of the Esophagus: A Case Report - Dawood, Tasneem; Zahir, Muhammad Nauman; Qureshi, Bilal Mazhar; Uddin, Zeeshan; Rashid, Yasmin Abdul; Jabbar, Adnan Abdul (Archives of Clinical and Medical Case Reports, 2022)
Background: Small cell carcinoma is an aggressive malignant tumor characterized by small-sized cells with scant cytoplasm, nuclei with finely granular chromatin and absent nucleoli, and a high mitotic count. The most common site is the lung which comprises 10-15 percent of all lung cancers. Rare sites of small cell carcinoma include the uterus, cervix, prostate, larynx, sweat glands, and gastrointestinal tract. No matter the site, it is an aggressive disease and is usually associated with a poor prognosis. Case Summary: We report the case of a 31-year-old gentleman, diagnosed with mixed small cell carcinoma and adenocarcinoma of the esophagus. He presented to our clinic with complaints of progressive dysphagia, cough, and weight loss for the last 6 months. An initial endoscopic biopsy was done, it was suspicious of mixed small cell carcinoma and adenocarcinoma of the esophagus which was reconfirmed by our histopathologist. MRI brain was negative. He was treated aggressively with Cisplatin and Etoposide-based concurrent chemo-radiation. He received 4 cycles of chemotherapy and 28 fractions of radiation sandwiched between cycles 2 and 4 of chemotherapy. He has been on surveillance since April 2019 and his most recent scan and upper GI endoscopy from May 2019 confirm that the disease is in remission. Conclusion: Mixed Small cell carcinoma and adenocarcinoma of the esophagus is an extremely unique, aggressive, and swiftly progressive disease, prone to distant metastasis and poor prognosis if left untreated. Treatment should be aggressive and commenced as soon as possible. Multi-modality management should be considered the current standard of care, to achieve both local and distant disease control.